New remains of Chambius kasserinensis from the Eocene of Tunisia and evaluation of proposed affinities for Macroscelidea (Mammalia, Afrotheria). (17th February 2018) - Tabuce, Rodolphe
Abstract: Chambius kasserinensis from the late Early or early Middle Eocene Chambi locality, central Tunisia, is undoubtedly the oldest known macroscelidid and possibly the basalmost representative of the order Macroscelidea. Hence, since its discovery in 1986, Chambius has played a key role in analyses focusing on afrotherian and eutherian phylogeny; for instance, as early as 1995, Butler's review of fossil macroscelideans highlighted the central position of Chambius in the origin of the order. Despite this, Chambius remained poorly known until recently. Here based on new mandibular fragments, well-preserved upper molars and CT scan analysis of the holotype maxilla, Chambius is revised. Its dentition is first described in detail, providing a precise characterization of the genus. Chambius is notably defined by a submolariform P4 with a three-cusped talonid, a reduced talonid on M2, and a prominent metaconule on M 1−2 . Interestingly, the two transverse lophs of the upper molars are basically formed by preconulecristae, evoking the recently defined peculiar bilophodonty of paenungulates. Comparisons with other Paleogene and modern macroscelidids, European Louisinidae, and North American Apheliscidae are also made, allowing the various hypotheses about the origin and early evolution of macroscelidids to be reviewed.